Impact of IT Investment on Indian and European Banks – An Analytical View - DAFANE, VIRENDRA (Digital Repository of Theses, 2024)
Currently, technology is the primary facilitator of the financial market. It can be easily said that financial services are driven by technology. The primary trend of financial unbundling has generated a paradigm shift, allowing the minor player to compete with big giant banks. Moreover, much research has been done, and it has been in the area of how digital transformation or emerging technologies or total IT investment impact the financial services market. The research has been done with a single entity like Blockchain, data, or cloud and their impact on a specific market. There is a potential gap in the research as the research is limited to one market and precise technology. This research aims to examine the impact of IT investment on Indian and European markets and compare them in terms of financial attributes. For example, the Cost to income ratio has varied for Indian and European banks from 2017 to 2022. This research has a hypothesis developed by theoretical aspects, which data-driven algorithms will test for validity. In the end, the study aims to understand the impact of IT investment on Indian and European banks and compare them.